Penerapan Algoritma Dempster Shaferberbasis Android Pada Sistem Pakar Untuk Mendiagnosa Kerusakan Motor Matic - Sumarni Adi; Ike Verawati (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Expert System is a computer-based system that combines knowledge, facts, and reasoning techniques in solving problems in a particular field like an expert. Expert systems can function as consultants who advise users as well as assistants to experts. One way to overcome and help detect a person's motor motor damage is to create an expert system based on Android as a media for consultation and monitoring so that the user understands what is happening with his motorbike. The Dempster Shafer method is a non monotonous reasoning method used to find inconsistencies due to the addition or subtraction of new facts that will change the existing rules, so the Dempster Shafer method allows one to be safe in doing the work of an expert in this matter is a mechanic. The purpose of this study was to apply the Dempster Shafer uncertainty method to the expert system to diagnose damage to the motorbike and also measure the accuracy of the Dempster Shafer inference engine. The diagnostic results of damage to the matic motor generated by the expert system are the same as the results of manual calculations using the Dempster Shafer inference engine theory which is processed from the results of interviews with the mechanic motor mechanic. So it can be concluded that an android-based expert system that has been built can be used to diagnose damage to the Matic motor. Keywords:Dempster Shafer, Motor Matic, Expert System, Android